Field notes contributed by Sharon Laub, fall 1991 - Laub, Sharonet al (1991)
List of birds and locations contributed by Sharon Laub. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed